UTILIZATION OF CONCRETE ROAD TEMPERATURE TO SUPPORT ELECTRICAL ENERGY USING A Z-SHAPED COPPER PLATE AS A THERMOELECTRIC GENERATOR - Harri Gunawan (TRAKSI, 2022)
As knowledge and technology increase, everyone will need electricity to carry out daily activities. Existing electrical energy sources are very limited. Various attempts were made to find new sources of electrical energy. One of them is a thermoelectric generator. Thermoelectric generators are electrical generator devices that convert heat (temperature difference) into electrical energy through the seeback effect. In this study, using 3 thermoelectric generator modules with type SP 1848 arranged in series with Z-shaped copper plates as heat receivers and  heatsink filled with water as a cooling medium. The research was carried out by utilizing the heat energy from a concrete road when exposed to solar radiation with a class III cast concrete type with K 450 placed on a medium with a size of 550 mm x 300 mm x 100 mm. The results of the research conducted show that the maximum power generated by using concrete produces a power of 15.21 mW when solar radiation is 1022 W / m2 . With energy that is generated continuously every day, it is possible for this research to be developed so that it can be used for alternative energy needs in the future.